Importancia de las zonas francas en colombia y su impacto en las empresas en los años 2020 y 2021 (2022)
This research is based on the importance of Free Zones and the impact they have generated for the companies that operate within them. Currently in Colombia the Free Zones are governed under decree 278 of 2021, which uses a new commitment from the Government to attract investment, hand in hand with the 120 that exist. In accordance with the foregoing, it is intended to demonstrate its operation and its legislation, to estimate its importance and impact on Colombian companies. On the other hand, it is also intended to explain the benefits and privileges that companies have, in order to be able to determine the advantages and disadvantages that they have; in addition to this, being able to see and analyze the imports and exports that are made from the Free Zones of Colombia, where a compilation of statistical data provided by public entities in Colombia such as PROCOLOMBIA and DANE will be carried out.